HUKUM POSITIVISME TERHADAP PEMBELAAN TERPAKSA DALAM KASUS PEMBEGALAN - Fendy Oktavianto; Jaury Douglas Pardomuan; Taufiqurrohman Syahuri (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The law aims to ensure the existence of legal certainty in society and the law must also be in harmony with justice, namely the principles of justice of that community, in order to avoid the existence of a crime in the community. In the standard legal system, the influence of positivism also appears, which is applied to all Indonesian citizens, especially in the field of criminal law. Several prominent cases, which have been reported by the media about criminalization of victims against criminal cases of self-defense. Self-defense can be interpreted as a process, a way or an act to prevent and also distance yourself from negative things that the defender does not want to get. The principle of self-defense is balance, namely the defense or self-resistance of a person to maintain his dignity, must be balanced or equal to the attack of the criminal perpetrator against him. So it is not at all permissible to defend in an excessive way. A problem then arises which is why law enforcement in Indonesia is more inclined to the principle of legal certainty, which the important meaning of this principle also has a similarity with the main idea that exists in the construction of legal positivism reasoning so that it looks as if it upholds the principle of community justice.